2003
DOI: 10.1021/ma0348573
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Self-Assembled Polyphenylene Dendrimer Nanofibers

Abstract: A second-generation polyphenylene dendrimer 1 self-assembles into nanofibers on various substrates such as HOPG, silicon, glass, and mica from different solvents. The investigation with noncontact atomic force microscopy (NCAFM) and scanning electron microscopy (SEM) shows that the morphology of the dendrimer nanofibers highly depends on substrate, solvent, and preparation method. Fluorescent nanofibers can be prepared from a polyphenylene dendrimer with chromophores either attached to the periphery of the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 66 publications
0
47
0
2
Order By: Relevance
“…Self-assembly has also been shown by molecules other than peptides or PAs [76]. For example, Liu et al reported the self-assembly of polyphenylene dendrimers into micrometer-long nano-fibers [77,78]. Perutz demonstrated the formation of nanotubes from polyglutamines [79][80][81].…”
Section: Self-assemblymentioning
confidence: 99%
“…Self-assembly has also been shown by molecules other than peptides or PAs [76]. For example, Liu et al reported the self-assembly of polyphenylene dendrimers into micrometer-long nano-fibers [77,78]. Perutz demonstrated the formation of nanotubes from polyglutamines [79][80][81].…”
Section: Self-assemblymentioning
confidence: 99%
“…[263,279,280] Dendrimers up to the fourth generation with biphenyl (for example, 106) or trans-azobenzene (for example, 89) cores have also been shown to give rise to such globular cluster or nanofibers. [281,282] The formation of nanofibers was found to be favored by lower dendrimer generations and more-separated dendrimer branches. The major driving forces for aggregation are p interactions between the dendrimers as a result of interdigitation of the branches.…”
Section: Afm Studies and Self-assembly Of Dendrimersmentioning
confidence: 99%
“…Long fluorescent nanofibers have been obtained from such an assembly of the third-generation dendrimer analogue of 116 and the secondgeneration dendrimer 122 bearing one PMI unit. [282] The emission from 122 is red-shifted relative to that of the solution and indicates that aggregation of the chromophores is occurring. In contrast, the dendrimer 123 with two dye units (Scheme 31) does not form such nanofibers, only nanorods.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…When the fluorophore is embedded in the dendrimer core, the emission of the fiber is similar to that of the isolated chromophores, due to shielding effect. In contrast, when the fluorophore is attached to the surface of the dendrimer, it suffers interactions with other peripheral fluorophores (Liu et al, 2003).…”
Section: Dendrimer-based Nanofibersmentioning
confidence: 99%